Recent progress and remaining challenges in organometallic halides based perovskite solar cells. (October 2017) - Mehmood, Umer; Al-Ahmed, Amir; Afzaal, Mohammad; Al-Sulaiman, Fahad A.; Daud, Muhammad
Abstract: The efficiency of perovskite solar cells (PSCs), based on thin film organometallic halides/mixed-halides, has rapidly increased from 3.8% in 2009 to 20.1% by 2015. Enhanced efficiency as well as the flexibility in material development and the structure are the primary reasons for their emergence in the photovoltaic market. Inherently distinctive properties of perovskite materials are mainly responsible for the enhanced efficiency. A variety of different techniques and device architecture have been employed for the fabrication of high-performance perovskite solar cells. As many parameters can be optimized, the efficiency of these devices can be further improved. This review highlights the intrinsic properties of lead halide perovskites and the recent progress in the application of these novel materials in producing efficient solar cells. Key factors affecting their solar performance are also highlighted. Scope and the need for lead free halide perovskites are also discussed.